STRATEGI PEMASARAN JAMUR TIRAM (Pleurotus Ostreatus) (Studi Kasus: Usaha Jamur Tiram Kus Mushroom di Kecamatan Seputih Surabaya Kabupaten Lampung Tengah) THE MARKETING STRATEGY OF OYSTER MUSHROOM (Pleurotus Ostreatus) (Case Study: Kus Mushroom Oyster Mushroom Business, in Seputih Surabaya District, Lampung Tengah Regency) - Fitriana, Elly; Suroso, Erdi; Nur, Muhammad; Al Rasyid, Harun (Jurusan Teknologi Hasil Pertanian, 2023)
Kus Mushrooms is a business that produces oyster mushrooms. This study aims to analyze internal and external factors that influence the marketing strategy of Kus Mushroom oyster mushrooms, formulate alternatives, and determine marketing strategy priorities for Kus Mushroom oyster mushrooms. The study uses QSPM analysis from the IFE, EFE, and SWOT matrixes. Based on the results of research using the IFE and EFE matrices, it can be seen that Kus Mushroom oyster mushrooms are in a strong position with a total IF matrix score of 3.06 and 2.74 and produce seven alternative strategies in the SWOT analysis. The priority strategy for Kus Mushroom oyster mushrooms is Utilizing quality products by diversifying products to increase added value and selling prices and expanding marketing reach through online promotion and marketing, with a total value of 6.96.